2011
DOI: 10.1111/j.1600-0838.2011.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic effect of hyperoxic recovery in elite swimmers performing high‐intensity intervals

Abstract: This investigation tested the hypothesis that breathing oxygen-enriched air (F(i)O(2) =1.00) during recovery enhances peak (P(peak)) and mean power (P(mean)) output during repeated high-intensity exercise. Twelve elite male swimmers (21 ± 3 years, 192.1 ± 5.9 cm, 79.1 ± 8.2 kg) inhaled either hyperoxic (HOX) or normoxic (NOX) air during 6-min recovery periods between five repetitions of high-intensity bench swimming, each involving 40 maximal armstrokes. Oxygen partial pressure (pO(2)) and saturation (SO(2)), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
3
24
0
2
Order By: Relevance
“…To date, only a few studies have focused on the effects of hyperoxic recovery from exercise on performance at sea level, and such research has produced inconsistent results (5,11,14,15,21,24,25,31). The current findings are in accordance with most studies on hyperoxic recovery, that hyperoxic air conditions resulted in no differences in power output (15,24) or performance time (21,31) after the inhalation of hyperoxic air (F i O 2 = 1.00) during periods of recovery from intervals of maximal exercise compared with normoxic air scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only a few studies have focused on the effects of hyperoxic recovery from exercise on performance at sea level, and such research has produced inconsistent results (5,11,14,15,21,24,25,31). The current findings are in accordance with most studies on hyperoxic recovery, that hyperoxic air conditions resulted in no differences in power output (15,24) or performance time (21,31) after the inhalation of hyperoxic air (F i O 2 = 1.00) during periods of recovery from intervals of maximal exercise compared with normoxic air scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Sperlich et al (25) reported that an elevated fractional content of inspired oxygen (F i O 2 ) during 6-min periods of recovery between 5 Â 50-s maximal arm strokes increased power output in elite swimmers. By contrast, performance was not enhanced by hyperoxic recovery between 5 Â 30-s maximal cycling sessions (24), between two incremental running tests until exhaustion (31), and between 6 Â 3-min high-intensity intervals on a kayak ergometer, with the session set at sea level (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is evidence that exposure to hyperoxia improves performance during continuous exercise for more than 3 min [24, 27, 33], the effects of hyperoxic gas inhalation on performance during intermittent exercise have been controversial [30]. Exercise performance was improved by inhalation of hyperoxic gas during 6-min recovery periods between five repetitions of high-intensity bench swimming [30], but not by inhalation of hyperoxic gas during 2-min recovery periods between six 3-min laboratory-based kayak ergometer sessions [22]. Our current results demonstrate that inhalation of hyperoxic gas during five entire 3-min sessions of high-intensity intermittent exercise alternated with 3-min rest periods improves exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of hyperoxic gas during exercise has been shown to counteract the reduction in S a O 2 that occurs during high-intensity intermittent exercise [21, 22, 30]. Nummela et al [21] reported that inhalation of hyperoxic gas (fraction of inspiratory oxygen (F i O 2 ) = 0.40) during an entire session of high-intensity intermittent exercise consisting of three sets of 300 m of running at different speeds on a treadmill, prevented S a O 2 levels from decreasing.…”
Section: Introductionmentioning
confidence: 99%